Peran Pelabuhan Belawan dalam Economic Sustainability terhadap Kota Medan yang Inklusif dan Global - M. Permata Akbar Pala Tandjung Akbar; Ibnu Zulian (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Belawan Port, as the most important port in western Indonesia, plays a vital role in supporting economic development at both regional and national levels. This study aims to explore the role and impact of Belawan Port in strengthening economic sustainability (economic, social, and environmental dimensions) toward an inclusive and global Medan City. The research applies a qualitative approach, including literature review, field observation, and interviews with relevant stakeholders. The findings reveal that Belawan Port functions beyond being merely a logistics and international trade hub. It serves as a driver of local economic growth by creating employment opportunities (economic), developing infrastructure, and improving regional connectivity (social and environmental). Nevertheless, several challenges remain, particularly concerning operational efficiency, cross-sectoral integration, and potential environmental impacts. Therefore, strengthening collaboration between government, business actors, and the community is essential to optimize the port’s role in promoting sustainable, inclusive economic growth aligned with Medan City’s vision as a global city.